Analisis Teknik Public Speaking Pada Stand Up Comedy Pada Komunitas Stand Up Indo Kudus - Husna, Indah; Rohimi, Primi (Institut Agama Islam Negeri Kerinci, 2024)
This study discusses the public speaking techniques used by members of the Stand Up Indo Kudus Community in their stand-up comedy performances. Public speaking in this context involves the skill of speaking in front of an audience with the aim of entertaining and building effective communication through humor. The study employs a descriptive qualitative approach using semi-structured interviews to gather in-depth data from active comedians within the community. The findings reveal that frequently used public speaking techniques include voice intonation control to emphasize punchlines, body language to strengthen the narrative, and eye contact to create interaction with the audience. Additionally, improvisation plays a crucial role in handling unexpected situations on stage. Through activities such as open mic sessions and group discussions, the community consistently develops its members’ communication skills, shaping confident, creative, and adaptive comedians in various situations